Hotel service, assumption and starter of the tourism development - Daliborka Blazeska; Vladanka Davkovska; Dejan Nakovski (UTMS Journal of Economics, 2016)
The tourism worldwide is continuously making high development ascent and the same is a result of the expansion in the hotel industry. About that is very remarkable the improvement of the working processes, i.e. the quality of the service, but also the construction of numerous new facilities, which together affects the competition on the international tourism market, where Republic of Macedonia also gives its national tourism product. This paper pays special attention to the hotel service and the staff which are its inevitable and irreplaceable factor, and on which depends the guest satisfaction. In this paper is emphasized the monitoring the satisfaction of the hotel guests with hotel service, in the hotel complexes. The results confirm that Republic of Macedonia is recognized on the tourism market for the great and unique hospitality of the population in general, but also of the tourism staff. But that doesn't mean that in future shouldn't be paid attention on even greater improvement of the services quality.
Keywords: L83; M31; M12; 330; staff; quality; competition